Bangladesh: Ending hunger and undernutrition: challenges and opportunities - Compact2025 (International Food Policy Research Institute, 2017)
A draft scoping report was prepared to inform the roundtable discussion by providing an overview of the food security and nutrition challenges and opportunities in Bangladesh. It reviews the current food security and nutrition policy landscape across key sectors and actors in Bangladesh as well as critical knowledge, policy, and implementation gaps. Additionally, the scoping report presents a SWOT analysis (strengths, weaknesses, opportunities, and threats) that crystallizes the main elements that drive or hamper food security and nutrition in the country. To determine what is holding back progress, this report identifies several key research and action gaps, including understanding linkages across agriculture and nutrition as well as between nutrition and social protection, and building the evidence base for impacts of key nutrition interventions.